Suitability of Different forest Species for Social Forestry Programme Under Different Soil Conditions Part II-lateritic Soil - Nath, S.; Das, P. K.; Gangopadhyay, S. K.; Singh, Balvinder; Banerjee, S. K. (Indian Forester, 1990)
Height and girth increment of different forest tree species planted along road-sides, canal and river banks, wastelands and along railway tracks have been studied and correlated with soil attributes of lateritic soil zone of Midnapore district, West Bengal. Some of the sites having better nutritional status accelerated the growth of some selected species. On the basis of the results some species have been identified and recommended for planting in the lateritic belt to meet the demand for fuel wood and fodder.